KEEFEKTIFAN MODEL PEMBELAJARAN FLIPPED CLASSROOM BERBANTU VIDEO PEMBELAJARAN UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA DAN KEMAMPUAN LITERASI NUMERASI SISWA KELAS VI GUGUS KI HAJAR DEWANTARA KEC. WONOTUNGGAL - Rifki Khamdani; Rasiman; Joko Sulianto (STKIP Subang, 2023)
The objectives to be achieved in this study are (1) to determine the effectiveness of the flipped classroom learning model assisted by video learning in increasing students' understanding of mathematical concepts, (2) to determine the effectiveness of the flipped classroom learning model assisted by video learning in improving students' numeracy literacy skills, (3) knowing factors supporting the implementation of the flipped classroom learning model assisted by video learning in improving students' understanding of mathematical concepts and numeracy literacy skills. This type of research is quasi-experimental research with the Nonequivalent Control Group Design. The population in this study were students in grade VI semester II of Penangkan Public Elementary School and Siwatu 01 Public Elementary School in the Ki Hajar Dewantara Cluster, Wonotunggal District, for the 2022/2023 academic year, with a total of 40 students. Data were obtained through test instruments and student response questionnaires. The results of the study prove that (1) learning statistics for class VI students using the flipped classroom learning model assisted by learning videos is effective in increasing students' understanding of mathematical concepts. (2) learning statistics for class VI students using the flipped classroom learning model assisted by learning videos effectively improves students' numeracy literacy skills. (3) there are factors that support the effectiveness of the flipped classroom learning model assisted by video learning in increasing students' understanding of mathematical concepts and numeracy literacy skills including teacher-facilitated learning, delivery of learning objectives, training self-confidence, video assistance can deepen understanding of the material, discover new knowledge and can learn anywhere and anytime.